Characteristics of pregnancy with Systemic Lupus Erythematosus (SLE) in Dr. Mohammad Hoesin Hospital, Palembang - Nyimas Aliyah Faizatun Muthmainnah; Nuswil Bernolian; Eddy Roflin; Cindy Kesty (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2021)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with complex pathogenesis with broad clinical manifestations, more common in women of reproductive age between 15-44 years, so there is an increased incidence in pregnancies. Methods: This study was a descriptive observational study with a cross-sectional design using medical records of patients in Dr. Mohammad Hoesin Hospital Palembang from January 2018-June 2020. Sampling was carried out by total sampling with the presentation of data in tables and narratives. Data processing was performed using SPSS 25. Results: There were 1,039 pregnancies in January 2018-June 2020 with 26 pregnancies with SLE and 8 patients (30.8%) of moderate degree SLE. The demographic characteristics were 26-30 age range (30.8%), high school education status (53.8%), the number of pregnancies 2-3 times (53.8%), the number of primiparous births (46.2%), and the number of miscarriages was never experienced (65.4%). Based on clinical signs and symptoms, malaise (15.4%), malar rash, photosensitivity spots and alopecia (15.4%), inflammatory arthritis (46.2%), lupus nephritis (11.5%), abdominal pain ( 34.6%), lymphadenopathy (3.8%), anemia or lymphopenia (15.4%), and cephalgia (7.7%). Meanwhile, the parameter of diagnosis was lymphopenia (15.4%), eGFR stage 1 (34.6%), proteinuria or proteinuria and cylindruria (11.5%), ANA test (+) (19.2%), anti-dsDNA test (+) (19.2%), and the complement test decreased (7.7%). Pregnancy outcomes were found to have intrauterine growth restriction (IUGR) (19.2%) and preeclampsia and IUGR (11.5%). Conclusion: From the 26 pregnant patients with SLE, most were found with a moderate degree. Most demographic characteristics were age range 26-30 years old, high school education status, number of pregnancies 2-3 times, primipara, and never miscarriage. Characteristics of clinical signs and symptoms most commonly found in patients were malaise, malar rash, photosensitivity spots and alopecia, inflammatory arthritis, and abdominal pain. The diagnosis parameters were lymphopenia, stage 1 eGFR, proteinuria or proteinuria and cylindruria, ANA test (+), and anti-dsDNA test (+). Most pregnancy outcome is intrauterine growth restriction (IUGR).